Comparison Between Cultivation and Sequencing Based Approaches for Microbiota Analysis in Swabs and Biopsies of Chronic Wounds - Mahnic, Aleksander; Breznik, Vesna; Bombek Ihan, Maja; Rupnik, Maja (Frontiers in Medicine, 2021)
Chronic wounds are a prominent health concern affecting 0.2% of individuals in the Western population. Microbial colonization and the consequent infection contribute significantly to the healing process. We have compared two methods, cultivation and 16S amplicon sequencing (16S-AS), for the characterization of bacterial populations in both swabs and biopsy tissues obtained from 45 chronic wounds. Using cultivation approach, we detected a total of 39 bacterial species, on average 2.89 per sample (SD=1.93), compared to 5.9 (SD=7.1) operational taxonomic units per sample obtained with 16S-AS. The concordance in detected bacteria between swab and biopsy specimens obtained from the same CWs was greater when using cultivation (58.4%) as compared to 16S-AS (25%). In the entire group of 45 biopsy samples concordance in detected bacterial genera between 16S-AS and cultivation-based approach was 36.4% and in swab samples 28.7%. Sequencing proved advantageous in comparison to the cultivation mainly in case of highly diverse microbial communities, where we could additionally detect numerous obligate and facultative anaerobic bacteria from genera Anaerococcus, Finegoldia, Porphyromonas, Morganella and Providencia. Comparing swabs and biopsy tissues we concluded, that neither sampling method shows significant advantage over the other regardless of the method used (16S-AS or cultivation). In this study, chronic wound microbiota could be distributed into three groups based on the bacterial community diversity. The chronic wound surface area was positively correlated with bacterial diversity in swab specimens but not in biopsy tissues. Larger chronic wound surface area was also associated with the presence of Pseudomonas in both biopsy and swab specimens. The presence of Corynebacterium species at the initial visit was the microbial marker most predictive of the unfavorable clinical outcome after one-year follow-up visit.